Imaging Modalities to Assess Oxygen Status in Glioblastoma - Corroyer-Dulmont, Aurélien; Chakhoyan, Ararat; Collet, Solène; Durand, Lucile; MacKenzie, Eric T.; Petit, Edwige; Bernaudin, Myriam; Touzani, Omar; Valable, Samuel (Frontiers in Medicine, 2015)
Hypoxia, the result of an inadequacy between a disorganized and functionally impaired vasculature and the metabolic demand of tumor cells is a feature of glioblastoma. Hypoxia promotes the aggressiveness of these tumors and, equally, negatively correlates with a decrease in outcome. Tools to characterize oxygen status are essential for the therapeutic management of patients with glioblastoma: i) to refine prognosis; ii) to adapt the treatment regimen; iii) and to assess the therapeutic efficacy. While methods that are focal and invasive in nature are of limited use, non-invasive imaging technologies have been developed. Each of these technologies is characterized by its singular advantages and limitations in terms of oxygenation status in glioblastoma. The aim of this short review is, first, to focus on the interest to characterize hypoxia for a better therapeutic management of patients and, second, to discuss recent and pertinent approaches for the assessment of oxygenation/hypoxia and their direct implication for patient care.